Wells Syndrome in Children: Case Study and Differential Diagnostics - Nikolay N. Murashkin; Eduard T. Ambarchian; Roman V. Epishev; Alexander I. Materikin; Leonid A. Opryatin; Roman A. Ivanov; Daria S. Kukoleva ("Paediatrician" Publishers LLC, 2020)
Background. Wells syndrome (eosinophilic cellulitis) is recurrent granulomatous dermatitis with peripheral blood eosinophilia. This is extremely rare pathology, therefore, there are no reliable epidemiological data on its prevalence. Only about 200 cases were recorded worldwide and 30 of them among children according to the meta-analysis (2012). The disease is mostly sporadic, there are rare family cases, according to the results of little number of scientific publications.Clinical Case Description. The clinical case of Wells syndrome in female 4 years old patient is presented. Clinical findings included symmetrical skin lesions, nodes and large irregular edematous plaques of red-purple color with clear fluid vesicles on its surface. The disease had wavy course: rashes have recovered spontaneously over 7-10 days, new elements appeared alongside with feeling unwell, fever up to 37,8°C and abdominal pain. Similar clinical findings of rashes were observed in paternal relatives of the child.Conclusion. Differential diagnostics of Wells syndrome should be carried out with skin granulomatous diseases and hypereosinophilic syndrome that may be characterized by similar clinical findings. Verification of Wells syndrome diagnosis is complicated due to its rareness, low awareness of dermatologists and pediatricians about this pathology, as well as ignoring the need to carry out histological tests during the disease exacerbation.